Struktura wielochorobowości w starszym wieku u osób przebywających w instytucjach opieki długoterminowej = The structure of multimorbidity in older age in residents of long-term care institutions - Chmielowiec, Krzysztof; Chmielowiec, Jolanta Zofia; Chmielewski, Piotr; Grzywacz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
On the basis of a cross-sectional study among residents of two long-term care centers in the Lubuskie Voivodeship (i.e., Dom Pomocy Społecznej (DPS) - a residential home in Zielona Góra and Zakład Opiekuńczo-Leczniczy - a psychiatric care and treatment institution in Ciborz), the authors determined multimorbidity and polypragmasy in people over 60. The study material consisted of the medical data of persons who had been residents of the two institutions till 2013. The differences between DOS and ZOL in the number of diseases and drugs taken were established by using the Pearson`s Chi-squared test and t-test.
Keywords: opieka długoterminowa; polipragmazja; wielochorobowość; osoby starsze; long-term care; polypragmasy; multimorbidity; olderly people